Cu-Al-Mn shape memory alloy based Schottky diode formed on Si - Aldirmaz, E.; Tataroglu, A.; Dere, A.; Guler, M.; Guler, E.; Karabulut, A.; Yakuphanoğlu, Fahrettin (Elsevier, 2019)
In this work, martensite was made over the wide temperature ranges and the two forms of martensite morphology in Cu85.41Al9.97Mn4.62 shape memory alloy (SMA) were beta' and gamma' martensite phases. The SMA was characterized by the use of X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyses. In order to fabricate the Schottky diode, Cu-Al-Mn alloy was used as a Schottky contact on p-type Si semiconductor substrate. Some of the crucial parameters for diodes such as ideality factor and barrier height values were obtained from electrical measurements. Illumination-dependent measurements showed that the fabricated device presents the behaviors of photodiode and photoconducting. Besides, it is found that the fabricated diode's structure is sensitive to illumination. Frequency-dependent measurements also indicated that the series resistance and interface state parameters are crucial to affect electrical characteristics of the fabricated diode. The experimental results showed that the fabricated Schottky device could be used in variety of optoelectronic applications.
Keywords: Cu-Al-Mn; Shape memory alloy; Schottky diode; Illumination measurement; Frequency dependence